Investigating the Usability and Acute Effects of a Bedside Video Console to Prefrontal Cortical Activity Alterations: A Preclinical Study in Healthy Elderly - Knols, Ruud H.; Swanenburg, Jaap; De Bon, Dino; Gennaro, Federico; Wolf, Martin; Krüger, Bernard; Bettex, Dominique; de Bruin, Eling D. (Frontiers in Systems Neuroscience, 2017)
Introduction Elderly people at risk of developing cognitive decline; e.g. following surgery, may benefit from structured, challenging, and repetitive cognitive video training. This study assessed usability and acute effects of a newly developed bedside console (COPHYCON). Material and Methods Fifteen healthy elderly individuals performed a one-time 80-minute intervention, including cognitive video games aimed at improving awareness and selective attention. Perceived usefulness and perceived ease of use (Technology Acceptance Model) were assessed together with measures of the achieved game level, reaction times, (in-) correct responses during ALERT and SELEKT game play. Further, prefrontal cortical involvement of the regional cerebral hemoglobin saturation (rS02%) assessed with functional near infrared spectroscopy (fNIRS) (n=5) and frequency bands of relative EEG recordings (n=10) was analyzed. Results All participants completed the study without any adverse events. Perceived usefulness and perceived ease of use (TAM scores range 1-7) of the system varied between 3.9 and 6.3. The game levels reached for awareness varied between 9-11(initial score 8-10), for reaction speed between 439ms and 469ms, and for correct responses between 74.1% and 78.8%. The highest level for the selective attention games was 2 (initial score 1), where reaction speed varied between 439ms and 469ms, correct responses between 96.2% and 98.5%, respectively. The decrease of rS02% in the right prefrontal cortex during gameplay was significantly (p<0.001) lower, compared to the left prefrontal cortex. Four participants yielded significant lower rS02% measures after exergaming with the ALERT games (p<.000), but not with the SELECT games. EEG recordings of theta power significantly decreased in the averaged ~0.25-0.75 time interval for the left prefrontal cortex sensor across the cognitive game levels between the ALERT 1 & SELECT 1, as well as between SELECT 1 & 2 games. Conclusions Participants rated the usability of the COPHYCON training positively. Further results indicate that video gaming may be an effective measure to affect prefrontal cortical functioning in elderly. The results warrant a clinical explorative study investigating the feasibility of the COPHYCON in a clinical setting. Keywords: Brain plasticity, Computerized Cognitive training, Cortex, Elderly, Exergames, Motor Control, Multisensory Integration, Neurorehabilitation